MACULAR PERIVENOUS RETINAL WHITENING AND PRESUMED RETINO–CILIARY SPARING IN A RECURRENT CENTRAL RETINAL VEIN OCCLUSION ASSOCIATED WITH THE ANTIPHOSPHOLIPID SYNDROME AND CRYOGLOBULINEMIA. Issue Volume 12:Issues 3(2018) (2018) - Sebrow, Dov B.; Jung, Jesse J.; Horowitz, Jason; Odel, Jeffrey G.; Freund, K. Bailey
Abstract : Purpose: Macular perivenous retinal whitening results from hypoperfusion-induced ischemia of the middle retina that can occur in central retinal vein occlusion (CRVO). We describe an unusual case of recurrent CRVO with macular perivenous retinal whitening and retino–ciliary venous sparing in the setting of 2 prothrombotic diseases, antiphospholipid syndrome and Type II cryoglobulinemia. Methods: A 50-year-old man presented with intermittent loss of vision in his right eye related to a recurrent CRVO. Color photography, optical coherence tomography, and fluorescein angiography were performed and compared with those obtained during a previous CRVO that occurred 6 years earlier in the same eye. Results: On presentation, visual acuity was hand motion in the right eye, 20/30 in the left eye. Funduscopic examination of the right eye showed vascular tortuosity, scattered retinal hemorrhages, and retinal whitening in the macula. Optical coherence tomography showed hyperreflectivity of the middle layers of the retina that correlated with the areas of retinal whitening. A discrete area of retinal sparing was noted in the superonasal macula that, on fluorescein angiography, corresponded to the distribution of a single retino–ciliary vein. A review of retinal imaging obtained during the patient's previous CRVO showed similar but more subtle findings of retino–ciliary sparing. Laboratory testing revealed antiphospholipid syndrome and Type II cryoglobulinemia. As the patient's CRVO progressed and subsequently stabilized after treatment in the following months, this area of venous sparing remained the only functional, nonischemic retinal tissue in his macula. Presumably, this vein possessed privileged and uncompromised blood flow by circumventing the occluded venous circulation. Conclusion: Macular perivenous retinal whitening should be considered in the differential diagnosis of retinal whitening and occurs in CRVO secondary to hypoperfusion-induced middle retinal ischemia. To our knowledge, this case represents the first description of retino–ciliary venous sparing of the retina in CRVO. Abstract : Hypercoagulability from antiphospholipid syndrome and Type II cryoglobulinemia may cause a central retinal vein occlusion with macular perivenous retinal whitening. Retino–ciliary veins, if present, can allow for sectoral retinal sparing from the surrounding ischemic insult.